A guide to the culture of science, technology, and medicine (The Free press,Collier Macmillan, 1980)
The heart of A Guide to the Culture of Science, Technology, and Medicine is a set of state-of-the-field surveys of nine academic disciplines that take as their object science, technology, and medicine. They are integrated in this volume by a focus on value issues in the sciences and biomedicine...